ANALYSIS OF DIFFERENT LEARNING BEHAVIORS AND LEVELS OF UNDERSTANDING OF STUDENTS IN PJKR STUDY PROGRAM ON LEARNING OUTCOMES IN THEORY AND PRACTICE COURSES - mislan; Teguh Trisno Wibowo (International Jurnal of Education Schoolars, 2022)
Learning is a process of transferring knowledge by lecturers to students with the aim of creating an interaction so that the learning process becomes effective . In addition, learning is also one of the parameters of an education. Basically, every learning process that is carried out is directed to achieve predetermined goals. Sampling was carried out on September 1-17 2022 with a total of 64 students using the method . The sampling technique used was purposive sampling , which is a sampling technique whose characteristics or characteristics are known in advance based on the characteristics or characteristics of the population. The criteria determined by the researchers were PJKR study program students who had taken the lecture process for 6 semesters. Assessment uses GPA for semester results. These students are the class of 2018 with a total of 44 students, for the class of 2019 with a total of 20 students. The results showed that the average score obtained in theory courses was 60.2 and in practical courses was 62.64. While the acquisition of the highest category was in theory courses, namely in the good category with a frequency of 23 students (36%) and in practical courses, namely in the good category with a frequency of 22 students (34.4%). The average value and the highest category based on percentage and frequency. The average score obtained in theory courses is 36.4 and in practical courses is 36.7. While the acquisition of the highest category was in theory courses, namely in the sufficient category with a frequency of 25 students (39%) and in practical courses, namely in the sufficient category with a frequency of 25 students (39%). For the value of students of the Physical Health and Recreation Education Study Program, an average score of 72.2 is obtained, the minimum value is 30 and the maximum score is 82.5. As for the Practice Course, an average score of 77.1 is obtained, a minimum score of 30 and a maximum score of 85.